2013
DOI: 10.3329/jasbs.v38i1.15326
|View full text |Cite
|
Sign up to set email alerts
|

Species composition of limnetic zooplankton from the southern coastal areas (Mathbaria and Bakerganj) in Bangladesh

Abstract: We studied the coastal zooplankton community structure of six waterbodies of Mathbaria and Bakerganj from January 2008 to June 2009. In total 35 zooplankton species were identified under 26 genera under 20 families under 8 orders from Mathbaria. Among them 6 were protozoans, 24 were rotifers, 3 were copepods, 1 was cladocerans and 1 was ostracods. From Bakergonj a total of 42 zooplankton species were identified under 23 genera under 17 Families under 7 orders. Among them 3 were protozoans, 25 were rotifers, 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 8 publications
0
19
0
1
Order By: Relevance
“…Rotifera species abundance from both the sites (Kalshi and Namapara) were highest compared to other groups and it indicates favourable environmental condition. Mozumder et al, (2012) observed highest abundance of rotifera from both Mathbaria pond (64.86%) and Bakerganj pond (60.98%) of Barishal division of Bangladesh. During dry season, high concentrated nutrient content in the water bodies may resulted in increased the density of zooplankton.…”
Section: Resultsmentioning
confidence: 85%
“…Rotifera species abundance from both the sites (Kalshi and Namapara) were highest compared to other groups and it indicates favourable environmental condition. Mozumder et al, (2012) observed highest abundance of rotifera from both Mathbaria pond (64.86%) and Bakerganj pond (60.98%) of Barishal division of Bangladesh. During dry season, high concentrated nutrient content in the water bodies may resulted in increased the density of zooplankton.…”
Section: Resultsmentioning
confidence: 85%
“…Rather, authors used google search images from different websites citing the image link. Some species spelling was not found in google search; the author corrected the spelling [49][50][51][52][53][54][55][56]. There are some work may be done by different University students and Professors, but the authors used only published articles.…”
Section: Limitationmentioning
confidence: 99%
“…Phylum: Rotifera Class: Monogononta Order: Ploima Family: Philodinidae Genus: Rotaria Species: Rotaria neptunia [21,42,50,54] 19.…”
Section: Rotaria Neptuniamentioning
confidence: 99%
See 2 more Smart Citations